ChemInform Abstract: Nanostructured Amorphous Nickel Boride for High‐Efficiency Electrocatalytic Hydrogen Evolution over a Broad pH Range. Issue 19 (21st April 2016) - Zeng, Min; Wang, Hao; Zhao, Chong; Wei, Jiake; Qi, Kuo; Wang, Wenlong; Bai, Xuedong
Abstract: Nanospheres (80 nm) of Ni—B alloy with a Ni:B ratio of 2.7:1 are prepared by electroless plating on a glassy carbon electrode (1 mg/cm 2 ) which prior to this is activated by applying a 2 V potential vs.